The Obvious and Illusory “Trace” of Saadi in Ivan Bunin’s Poetry (Source Studies Aspect) - Anton V. Bakuntsev (Studia Litterarum)
The article is devoted to the identification and analysis of publications in which Ivan Bunin drew literary material for the poems “The Skull” (1907), “The Persian Wisdom” (1913), “The Testament of Saadi” (1913), which are still considered translations of excerpts from Saadi’s books “Bustan” (1257) and “Gulistan” (1258). The research uses the principle of historicism and the method of comparative analysis. The article demonstrates that: 1) when writing his poems, Bunin worked not only with classical ones that appeared by the end of the 19th and the beginning of the 20th centuries translations of Saadi’s books into Russian and the main European languages but also with relevant scientific and popular science literature; 2) the listed Bunin’s poems are not translations, but paraphrases of individual passages from “Bustan” and “Gulistan”; 3) in these poems, Saadi’s parables and maxims have undergone quite significant creative processing; 4) the poems “The Throne of Solomon” (1907) and “The Law” (1907), attributed by some researchers to Bunin’s works, in which it is also possible to “highlight the ‘trace’ of Saadi” (the expression by R.M. Safiulina), are based only on the texts of the Koran.